2015
DOI: 10.1007/s00294-015-0506-x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing mechanisms orchestrating post-transcriptional gene expression: intron retention and the intron-rich genome of apicomplexan parasites

Abstract: Apicomplexan parasites including Toxoplasma gondii and Plasmodium species have complex life cycles that include multiple hosts and differentiation through several morphologically distinct stages requiring marked changes in gene expression. This review highlights emerging evidence implicating regulation of mRNA splicing as a mechanism to prime these parasites for rapid gene expression upon differentiation. We summarize the most important insights in alternative splicing including its role in regulating gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…As one of major fields of enquiry in the post-genomic era, AS has been investigated in an increasing number of species over the past decade (Kalsotra and Cooper, 2011; Filichkin et al, 2015; Lunghi et al, 2016). It has been shown that AS plays a crucial role in enhancing transcriptomic and proteomic diversity, and its prevalence and characteristics vary considerably at many different levels, such as in species, tissues, and developmental stage (Kornblihtt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of major fields of enquiry in the post-genomic era, AS has been investigated in an increasing number of species over the past decade (Kalsotra and Cooper, 2011; Filichkin et al, 2015; Lunghi et al, 2016). It has been shown that AS plays a crucial role in enhancing transcriptomic and proteomic diversity, and its prevalence and characteristics vary considerably at many different levels, such as in species, tissues, and developmental stage (Kornblihtt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that intron retention, but not exon skipping, was the predominant AS type in protoscoleces based on our high-coverage poly(A) + RNA-Seq data. The advent of new sequencing technologies and algorithms is providing growing evidence that intron retention is a universal mechanism common to many eukaryotic organisms (Lunghi et al, 2016). By applying a new pipeline for intron-retention detection to high-coverage poly(A) + RNA-Seq data, Braunschweig et al (2014) found that intron retention is far more frequent in mammals than previously believed, affecting transcripts from as many as three-quarters of intron-containing genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous study demonstrated that introns serve a critical role in transcriptional regulation ( 44 ). Introns are not only involved in the formation of microRNAs and small nucleolar RNAs, but also regulate alternative splicing and affect the mRNA level ( 45 ). In the present study, the shRNAs targeting exons and introns effectively inhibited the expression of survivin in HeLa cells and increased the apoptosis rate, inducing marked apoptotic morphological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also have shown that unproductive splicing events prevent mRNA translation (e.g., no-go, non-sense-mediated, and nonstop decay) (32)(33)(34). Over the past decade, more examples of this phenomenon have been revealed, and it has been shown that alternative splicing produces structurally and functionally distinct mRNA and proteins, which enhance transcriptome and proteome diversity in humans considerably (35)(36)(37). Recent studies have indicated that .95% of human genes undergo alternative splicing and that many point mutations that result in human genetic disease have disrupted splicing (38,39).…”
Section: Discussionmentioning
confidence: 99%